Lesser Tuberosity Osteotomy Versus Soft-Tissue Subscapularis Release in Shoulder Arthroplasty. Issue 2 (June 2015) - Cagle, Paul J.; Patton, Jason G.; Beck, Ryan T.; Braman, Jonathan
<x xml:space="preserve">Abstract</x> Shoulder arthroplasty procedures continued to increase in prevalence, and controversy still remains about the optimal method to manage the subscapularis. Our study reviewed the available literature clinically comparing subscapularis approaches. A systematic review was conducted using MEDLINE, PubMed, and Cochrane Central Register of Controlled Trials. All clinical trials were identified, and trials comparing at least 2 different subscapularis approaches were examined. Six clinical trials were identified comparing lesser tuberosity osteotomy, subscapularis tenotomy, and peel. Two were randomized-controlled trials comparing osteotomy and peel. Both trials demonstrated improvements in both the groups without demonstrating a significant advantage to either approach. Four trials retrospective analyzed subscapularis osteotomy compared with tenotomy. These trials demonstrate a tendency for improved clinical function with subscapularis osteotomy when patients perform a belly-press test or shirt tuck. Level I and II studies have not shown a significant difference between soft-tissue and bony subscapularis approach with shoulder arthroplasty, but retrospective studies have suggested improved clinical outcomes with osteotomy. Level of evidence: Level IV systematic review of level III and IV studies.